Quantum theory of matter a novel introduction - Modinos, A. 1938- (John Wiley & Sons, 1996)
With a minimum of mathematics, this book provides a novel approach to the teaching of quantum mechanics. As many books mainly present the concepts of quantum theory, this volume emphasises the application of the theory, offering the reader a unifying picture of atoms, molecules and solids. Essential for all undergraduate physics courses, it will also be a most valuable supplementary text for postgraduate courses on quantum mechanics.